Linguistic Variation and Change in 250 Years of English Scientific Writing: A Data-Driven Approach - Bizzoni, Yuri; Degaetano-Ortlieb, Stefania; Fankhauser, Peter; Teich, Elke (Frontiers in Artificial Intelligence, 2020)
We trace the evolution of Scientific English through the Late Modernperiod to modern time on the basis of a comprehensive corpus composedof the Transactions and Proceedings of the Royal Society of London, thefirst and longest-running English scientific journal established in 1665.Specifically, we explore the linguistic imprints of specialization and di-versification in the science domain which accumulate in the formation of"scientific language" and field-specific sublanguages/registers (chemistry,biology etc).We pursue an exploratory, data-driven approach using state-of-the-art computational language models and combine them with selectedinformation-theoretic measures (entropy, relative entropy) for comparingmodels along relevant dimensions of variation (time, register). Focusing onselected linguistic variables (lexis, grammar), we show how we deploy com-putational language models for capturing linguistic variation and changeand discuss benefits and limitations.